"They Were Always Men, Writing About Men": Gender Representations in the Military Camps of the Southern Border in the Late 19th Century: "They Were Always Men, Writing About Men": Gender Representations in the Military Camps of the Southern Border in the Late 19th Century (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
This article examines gender representations in the 19th-century frontier documentation and literature, focusing on women in military camps. Through the analysis of period accounts, letters, and testimonies, it explores the roles and gender constructions presented in these texts, and how they reflect the social, political, and cultural tensions of the time. The article addresses the invisibility of women in conventional historical narratives and how, despite their marginalization, women played key roles in the daily life of military camps. This work aims to highlight the significance of women in these contexts and how gender representations shaped the historical memory of the frontier.
Keywords: Gender representations- Frontier- Women- Military camps